2015
DOI: 10.1136/practneurol-2015-001191
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial disease: mimics and chameleons

Abstract: Mitochondrial diseases are inherited disorders of oxidative phosphorylation that present with a multitude of clinical features in different combinations and with various inheritance patterns. To complicate the issue further, the clinical features of mitochondrial disorders overlap with common neurological and non-neurological diseases. This presents a diagnostic challenge: when is a rare mitochondrial disease responsible for a more 'common or garden' neurological presentation, and how often are neurologists mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
0
6
0
10
Order By: Relevance
“…For further support, we examined the relationship between TEs and the gene expression network of the fetal brain. We analysed 284 RNA-seq datasets from differing brain regions in the cortex and cerebellum of 172 fetal brains (post-conceptual week 4-17; mean 10.05 weeks) 40 . Identifying 20 unique modules in 6,766 differentially expressed genes (log2FC > 1, P value < 0.05), we observed that ape-specific hPGC-methylated TEs were primarily enriched in cortically expressed modules compared to those in the cerebellum (Extended Data Fig.…”
Section: Te-derived Enhancers May Facilitate the Development Of The Hmentioning
confidence: 99%
“…For further support, we examined the relationship between TEs and the gene expression network of the fetal brain. We analysed 284 RNA-seq datasets from differing brain regions in the cortex and cerebellum of 172 fetal brains (post-conceptual week 4-17; mean 10.05 weeks) 40 . Identifying 20 unique modules in 6,766 differentially expressed genes (log2FC > 1, P value < 0.05), we observed that ape-specific hPGC-methylated TEs were primarily enriched in cortically expressed modules compared to those in the cerebellum (Extended Data Fig.…”
Section: Te-derived Enhancers May Facilitate the Development Of The Hmentioning
confidence: 99%
“…РОССИЙСКИЙ ВЕСТНИК ПЕРИНАТОЛОГИИ И ПЕДИАТРИИ, 3,2016 ROSSIYSKIY VESTNIK PERINATOLOGII I PEDIATRII, 3,2016 В качестве иллюстрации приводим истории бо-лезней двух пациентов из не родственных друг другу семей с клинически различными формами митохон-дриального заболевания, обусловленными одинако-вой мутацией в гене POLG1 (p.L304R).…”
Section: оригинальные статьи наследственные болезниunclassified
“…РОССИЙСКИЙ ВЕСТНИК ПЕРИНАТОЛОГИИ И ПЕДИАТРИИ, 3,2016 ROSSIYSKIY VESTNIK PERINATOLOGII I PEDIATRII, 3,2016 На основании совокупности данных анамнеза, клинических проявлений и результатов обследо-вания у ребенка был в первую очередь заподозрен митохондриальный синдром MELAS 1 . В отделении девочка получала препараты карнитина, нейро-мультивит, коэнзим Q 10 , цитохром С, начата терапия L-аргинином.…”
Section: наблюдениеunclassified
See 2 more Smart Citations